2019
DOI: 10.1038/s41598-019-51872-9
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide differential expression profiling of lncRNAs and mRNAs associated with early diabetic cardiomyopathy

Abstract: Diabetic cardiomyopathy is one of the main causes of heart failure and death in patients with diabetes. There are no effective approaches to preventing its development in the clinic. Long noncoding RNAs (lncRNA) are increasingly recognized as important molecular players in cardiovascular disease. Herein we investigated the profiling of cardiac lncRNA and mRNA expression in type 2 diabetic db/db mice with and without early diabetic cardiomyopathy. We found that db/db mice developed cardiac hypertrophy with norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 54 publications
1
32
0
Order By: Relevance
“…LncRNAs are a type of endogenous RNA transcripts longer than 200 nucleotides which epigenetically regulate gene expression but do not have protein-coding potential. To our knowledge, it has found that lncRNAs are aberrantly expressed in DCM, leading to a variety of pathophysiological processes (Pant et al, 2019). LncRNA-MIAT has been first identified to be associated with myocardial infarction in a genome-wide association study in 2006 (Ishii et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs are a type of endogenous RNA transcripts longer than 200 nucleotides which epigenetically regulate gene expression but do not have protein-coding potential. To our knowledge, it has found that lncRNAs are aberrantly expressed in DCM, leading to a variety of pathophysiological processes (Pant et al, 2019). LncRNA-MIAT has been first identified to be associated with myocardial infarction in a genome-wide association study in 2006 (Ishii et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs have been recognized as being closely related to a variety of diseases, such as the occurrence, development, and prognosis of malignant tumors, cardiovascular diseases, and endocrine diseases, and have played important roles in regulating physiological processes such as cell proliferation, differentiation, and apoptosis. [2][3][4][5][6][7] Therefore, further research and verification of the role of abnormal lncRNA expression in HCC may provide novel ideas for the treatment of HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Long noncoding RNAs (lncRNAs) are a class of noncoding RNAs with a length greater than 200 nucleotides [ 6 ] and are categorized based on regulating gene expression in cis versus performing functions in trans [ 7 ]. In recent years, emerging evidence has shown that lncRNAs play major roles in the occurrence and development of cardiovascular disease [ 8 ], cardiomyopathy [ 9 ] and mesenchymal stem cells [ 10 , 11 ], in particular, dysregulation of lncRNAs has been discovered in many human cancers [ 12 14 ]. For example, HOX transcript antisense RNA (HOTAIR) is the first lncRNA [ 15 ] demonstrated to have a trans -transcriptional regulatory function, and it has been shown to have carcinogenic function in prostate cancer [ 16 ] and breast cancer [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%